2008
DOI: 10.1038/jhh.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between metabolic syndrome and left ventricular mass in hypertensive patients: does sex matter?

Abstract: Several studies documented an association between metabolic syndrome (MetS) and left ventricular (LV) hypertrophy. However, only in a few of these studies the impact of MetS on left ventricular mass (LVM) was separately analysed by gender, with conflicting results. The aim of our study was to verify, in a wide sample of essential hypertensive patients, the influence of gender, if any, on the relationship between MetS and LVM. We enrolled 475 non-diabetic subjects (mean age: 46 ± 11 years), with mild-to-moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…3 Indeed, in our study men with the metabolic syndrome had a significant 9% increase in LV mass index than men without the syndrome (50.3 vs 46.1 g  m À2.7 , P ¼ 0.002), whereas this difference was as large as 24% in women (49.5 vs 40.0 g  m À2.7 , Po0.001), and gender was found to be a significant effect modifier of the relation between the metabolic syndrome and LV mass. 3 However, a closer look at the data by Mulè et al 1 shows that the percent increase in LV mass in the subjects with the metabolic syndrome was more pronounced among women ( þ 27%) than among men ( þ 16%). Although not significant, the effect of the interaction term 'gender  metabolic syndrome' bordered statistical significance (P ¼ 0.10, in a multivariate model).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…3 Indeed, in our study men with the metabolic syndrome had a significant 9% increase in LV mass index than men without the syndrome (50.3 vs 46.1 g  m À2.7 , P ¼ 0.002), whereas this difference was as large as 24% in women (49.5 vs 40.0 g  m À2.7 , Po0.001), and gender was found to be a significant effect modifier of the relation between the metabolic syndrome and LV mass. 3 However, a closer look at the data by Mulè et al 1 shows that the percent increase in LV mass in the subjects with the metabolic syndrome was more pronounced among women ( þ 27%) than among men ( þ 16%). Although not significant, the effect of the interaction term 'gender  metabolic syndrome' bordered statistical significance (P ¼ 0.10, in a multivariate model).…”
mentioning
confidence: 97%
“…We read with interest the article by Mulè et al, 1 which explores the issue of the potential influence of gender on the relationship between the metabolic syndrome and and left ventricular (LV) mass. The Authors conclude that gender has no discernible effect on the above relation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 Diabetes mellitus accelerates the development of LVH in patients with essential hypertension independent of arterial pressure. 4 In this issue of the Journal of Human Hypertension, Cuspidi et al 6 show that metabolic syndrome (MS) also accelerates the development of LVH, as hypertensive patients of both genders had more cardiac alterations when they have MS.Earlier studies have shown that hypertensive patients with MS are more susceptible to develop LVH than those without MS. 7-10 Mule et al 9 showed in 475 non-diabetic subjects with mild-to-moderate essential hypertension, of whom 40% had MS, that left ventricular mass was significantly higher in those with MS than in those without it. The relationship between MS and left ventricular mass was not affected by gender.…”
mentioning
confidence: 99%